The digital art therapy frame: creating a 'magic circle' in teletherapy. Issue 3 (3rd July 2021) - Snyder, Kathryn
ABSTRACT: Background: There has been increasing attention to the use of teletherapy in art therapy with accessibility at the forefront of the argument for its use. Concerns have persisted around how to use art materials and media for therapeutic gain in a digital platform. The debate quickly needed to be reconsidered as the shutdown orders surrounding COVID-19 forced many of us to adopt online art therapy practice. Context: My child, teen and family art therapy outpatient practice in the Northeast United States, quickly pivoted online in late March. This move entailed establishing a new framework for creating a 'magic circle' for emotional resonance to create positive change. Approach: Adapting a new framework, we established routines and rituals for engaging even our youngest clients. Ethics and boundaries needed to be established in a new landscape of service delivery. Outcomes: Adaptation enabled us to work with our clients. While many things worked, art making and responsiveness to client needs proved to be challenges, along with the limits of technology and other distractions. Conclusions: We are now more adept, have developed shared art tools, and can assess how to build a working alliance for online art therapy practice. Implications for research: Massive use of online art therapy affords us the opportunity to look at how it may operate in a virtual world. Research may parse out best practices, what doesn't work, and for whom it might work best, and look at issues surrounding working alliance, therapist responsiveness and sensory processes in online art therapy. Plain-language summary: The world-wide pandemic of 2020 forced therapists to provide services online. My art therapy practice was no exception. We immediately had to pivot our child-centered art therapy services to online platforms and adapt our approach. The 'magic circle' framework that we create through our physical space, presence and three modes of engagement during art therapy were translated into telehealth. This framework is explained with two case vignettes to suggest both challenges to online art therapy practice as well as the success of the new model. Implications for research are discussed.